The Rise of Northern Unionism’s Influence on the Political Scene of Great Britain Against the Backdrop of Belfast’s Social and Economic Transformations During the Great War - Pawłowska, Antonina (Faces of War, 2025)
This article examines the situation in Belfast during the First World War, considering its role as the political and economic centre of the north of Ireland. It explores whether the global conflict contributed to the city’s development or led to its stagnation, focusing on three key aspects: economic, social, and political. The economic analysis particularly highlights the state of the shipbuilding industry. The study of social conditions reveals the economic, religious, and cultural sources of divisions among Belfast’s residents and shipyard workers. Meanwhile, the discussion of the political aspect traces key transformations within the Irish unionist movement, mainly its faction closely linked to Ulster and Belfast. The article aims to outline the situation in north of Ireland during the Great War to explain the causes of the growing social divisions in the interwar period, which ultimately led to the establishment of an administratively separate Northern Ireland.